2014
DOI: 10.1002/14651858.cd007284.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Types of intraocular lenses for cataract surgery in eyes with uveitis

Abstract: Background Cataract formation often occurs in people with uveitis. It is unclear which intraocular lens (IOL) type is optimal for use in cataract surgery for eyes with uveitis. Objectives To summarize the effects of different IOLs on visual acuity, other visual outcomes, and quality of life in people with uveitis. Search methods We searched CENTRAL (which contains the Cochrane Eyes and Vision Group Trials Register) (The Cochrane Library 2013, Issue 7), Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 45 publications
1
17
0
1
Order By: Relevance
“…This is interesting, as there appears to be a concern that an IOL may trigger intraocular inflammation in uveitic eyes [17]. Our results are consistent with a Cochrane review which concluded that there was uncertainty regarding the optimal IOL type during uveitic cataract surgery [18].…”
Section: Discussionsupporting
confidence: 83%
“…This is interesting, as there appears to be a concern that an IOL may trigger intraocular inflammation in uveitic eyes [17]. Our results are consistent with a Cochrane review which concluded that there was uncertainty regarding the optimal IOL type during uveitic cataract surgery [18].…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of PCO is significantly higher with polymethyl metha acrylate IOLs as compared with acrylic IOLs, and PCO rates do not significantly differ between hydrophobic or hydrophilic acrylic IOLs at 6 months' follow-up. 18,19 The lower incidence of PCO in the present study could be explained by the fact most cases had acrylic IOLs implanted within the capsular bag.…”
Section: Discussionmentioning
confidence: 56%
“…They suggested that a lens with a sharp optic edge had better visual outcomes in uveitic eyes because of reduced incidence of PCO [ 45 ]. A Cochrane review by Leung et al on types of intraocular lenses for cataract surgery in uveitis included four studies with a patient profile of adult uveitic eyes [ 42 , 46 49 ]. They concluded that there was uncertainty as to which type of IOL gave best visual and clinical outcomes in uveitic cataract surgery based on existing studies and advocated a multicenter international study.…”
Section: Reviewmentioning
confidence: 99%